2010 International Conference on Power System Technology 2010
DOI: 10.1109/powercon.2010.5666582
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of hydroelectric power plants' governor settings on low frequency inter area oscillations

Abstract: The Turkish TSO (TEIAS) has been leading a project that aims the synchronous interconnected operation of the Turkish Power System and the ENTSO-E CESA (former UCTE) System. For this purpose, this study concentrates on the specific problems related to the electromechanical systems of large size hydroelectric power plants regarding low frequency inter area oscillations, which are prone to occur once the interconnected operation is established. The expected frequency of inter area oscillations after interconnecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This situation violates the regulations in the guide and the PSS cannot be put into operation. Moreover, turbine governor system may also bring negative damping torque to decrease the damping of the LFO [26], and make this contradiction more serious.…”
Section: Problem Phenomenonmentioning
confidence: 99%
“…This situation violates the regulations in the guide and the PSS cannot be put into operation. Moreover, turbine governor system may also bring negative damping torque to decrease the damping of the LFO [26], and make this contradiction more serious.…”
Section: Problem Phenomenonmentioning
confidence: 99%
“…This tool can be used to investigate how various parameters of the turbine and governor influence various eigenvalues, including how sensitive the oscillation frequency is to changes in governor or turbine parameters [2], [3], [4] & [8].We performed a sensitivity analysis for the governor parameters of governor GOV1, which is associated with synchronous machine G1, and the simulation results obtained are similar to those of all other governors. The simulation results are given in Table 6.…”
Section: B Sensitivity Analysis Of Governor Parametersmentioning
confidence: 99%
“…The results showed that the parameters of hydro-turbines and governor speed influence the oscillation modes and proposed a further study of the hydraulic system, including the water system, hydro-turbine, and governor, to ensure a detailed analysis of the low-frequency oscillations in a hydropower plant's power system [2]. An assessment of the effect that hydroelectric power plants' governor settings have on low-frequency inter-area oscillations close to 0.15Hz was also carried out [3]. It proposed that removing sources of negative damping would significantly enhance the system's damping performance.…”
Section: Introductionmentioning
confidence: 99%
“…Such oscillations may cause excessive power swings between the synchronous zones, which may end up with the split of Turkish network from the ENTSO-E CESA system due to special protective measures that have been taken in Turkey in order to mitigate the spread of the event [13][14][15][16]. Indeed, after realization of the interconnection, observation of such inter-area oscillations by widearea measurement systems (WAMS) has verified this concern.…”
Section: Application Of the Proposed Strategy To Turkish Power Systemmentioning
confidence: 99%